Team formation in a network - Markus Kinateder (Fondazione Eni Enrico Mattei (FEEM), 2009)
Two project leaders (or entrepreneurs) in a network, which captures social relations, recruit players in a strategic, competitive and time-limited process. Each team has an optimal size depending on the project's quality. This is a random variable with a commonly known distribution. Only the corresponding project leader observes its realization. Any decision is only observed by the involved agents. The set of pure strategy Sequential Equilibria is characterized by giving an algorithm that selects one equilibrium at a time. An agent's expected payoff is related to his position in the network, though no centrality measure in the literature captures this relation. A social planner frequently would achieve a higher welfare.
Keywords: C72; C73; D85; 330; Dynamic Competitive Group Formation; Imperfect Information